DINAMIKA LAHIRNYA FATWA MUI PROVINSI MALUKU UTARA TENTANG SESATNYA SYI'AH JA'FARIYAH AJARAN NAWAWI HUSNI (ONG) - Ibnu Hasan Muchtar (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
The objective of this research is to describe the presence of synergy between the fatwa Commission of MUI of North Maluku and other fatwa institutions within Islamic organisations in issuing a fatwa on the deviation of Ja’fariya Shi’ism of Nawawi Husni (Ong). This is also to identify factors which lead to the synergy, and conversely, other obstacles that did not lead them to synergy.The research applied qualitative approach with descriptive analysis. The qualitative data is collected by using techniques of interview, documentary study, and library inquiry. The case of the study is the fatwa of MUI of North Maluku, No. 45, Year 2015 on the deviation of teaching spread by Nawawi Husni (Ong) on behalf of Ja’fariya Shi’ism.The research discovers that there was no synergy between the fatwa Commission of MUI of North Maluku and other fatwa institutions within Islamic organisations. The fatwa Commission of MUI of North Maluku did not officially involve other fatwa institutions within Islamic organisations when discussing the draft of the fatwa, well in fact, they were usually involved in the previous meetings before the idea whether the MUI need to issue a fatwa or not. This includes several factors such as 1) the emergency situation as the inter-citizen conflict had emerged; 2) it was not easy to coordinate with other fatwa institutions; 3) the have been representatives of Islamic organisations in the board of MUI of the Province of North Maluku